2018
DOI: 10.18410/jebmh/2018/626
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Vaginal Vault Parameters in Stratified Age Groups and Its Social Relevance in a South Indian Population

Abstract: BACKGROUNDThe vagina and endometrium show varying thickness in response to sex steroids. The vaginal wall layers have oestrogen receptors. This study uses technique described by Balica A. et al.The aim is to compute the two parameters, VMT and VWT in different age groups using transabdominal ultrasonography. Oestrogen regulates growth and function of the vaginal layers, demonstrated in laboratory animal studies. Only few articles describe these parameters.The aim of the study is to compute the two parameters, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…[7][8][9][10] Studies with designs similar to our study have found that vaginal mucosa and vaginal wall thickness decreases with menopause. 11,15 However, it should be kept in mind that women with in menopausal age may have higher rates for chronic diseases and higher BMI and diabetes rates may lead to inaccurate results or inadequate evaluation for measurement of TVT and TMT because of increase subcutaneous adipose tissue.…”
Section: Specificitymentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9][10] Studies with designs similar to our study have found that vaginal mucosa and vaginal wall thickness decreases with menopause. 11,15 However, it should be kept in mind that women with in menopausal age may have higher rates for chronic diseases and higher BMI and diabetes rates may lead to inaccurate results or inadequate evaluation for measurement of TVT and TMT because of increase subcutaneous adipose tissue.…”
Section: Specificitymentioning
confidence: 99%
“…10 Subsequently, certain publications have used vaginal wall and vaginal mucosal thickness to predict vaginal atrophy. 11,12 This study aimed to evaluate the use of transabdominal ultrasound and to determine the cutoff values for both transvaginal and transmucosal thickness for predicting VVA which is the most common symptom of GSM, without the requirement for vaginal examination that may cause pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation